2015
DOI: 10.1080/00438243.2015.1074871
|View full text |Cite
|
Sign up to set email alerts
|

The visual brain and the early depiction of animals in Europe and Southeast Asia

Abstract: The recent discovery that iconic depictions in caves on the Indonesian island of Sulawesi are more ancient than those from Upper Palaeolithic Europe raises questions as to when such images first arose and why the graphic outcomes from the two locations are so similar. In this paper, we show that these questions can be addressed by exploiting the extensive research carried out over the recent past on the psychology of perception and the neuroscience of the visual brain that allows the proper place of iconic dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…These universal art preferences nicely match predictions about universal human preferences that affected the fitness of our Pleistocene ancestors (Dissanayake 1998), and are believed to have been selected in order to guide habitat choice, hunting , predator avoidance as well as peer and mate choice (Barrett 2005;Falk and Balling 2010;Little, Jones and DeBruine 2011;New, Cosmides and Tooby 2007;Orians and Heerwagen 1992;Windhager et al 2011;Yang et al 2012). The universality and antiquity of these art preferences is further supported by prehistoric rock art and sculpture (dated at about 35,000 BP), In which animal and human figures are featured predominately in antipodal regions of the world (Hodgson and Watson 2015;Verpooten and Nelissen 2010). Focusing on the motivational system underlying art appreciation and production within this framework, Pinker (1997) suggested that art has evolved because it pushes, so to speak, our naturally selected "pleasure buttons".…”
Section: Evolutionary Aestheticsmentioning
confidence: 99%
“…These universal art preferences nicely match predictions about universal human preferences that affected the fitness of our Pleistocene ancestors (Dissanayake 1998), and are believed to have been selected in order to guide habitat choice, hunting , predator avoidance as well as peer and mate choice (Barrett 2005;Falk and Balling 2010;Little, Jones and DeBruine 2011;New, Cosmides and Tooby 2007;Orians and Heerwagen 1992;Windhager et al 2011;Yang et al 2012). The universality and antiquity of these art preferences is further supported by prehistoric rock art and sculpture (dated at about 35,000 BP), In which animal and human figures are featured predominately in antipodal regions of the world (Hodgson and Watson 2015;Verpooten and Nelissen 2010). Focusing on the motivational system underlying art appreciation and production within this framework, Pinker (1997) suggested that art has evolved because it pushes, so to speak, our naturally selected "pleasure buttons".…”
Section: Evolutionary Aestheticsmentioning
confidence: 99%
“…The point should be reinforced here that, although the caves provided a particularly resonant environment where natural features were exploited for depictive purposes, the fact that such features were also incorporated into animal representations throughout the world in rock- shelters and outdoor sites (Taçon et al 2014)—which are also prone to shifting light conditions—suggests that the same dynamic interaction between the material world and the highly sensitive visual system of hunters for perceiving animals was at work in the wider landscape (Hodgson 2008; Hodgson & Watson 2015). A large number of engravings of animals from the open-air sites of Foz Côa and Siega Verde have also been found that incorporate predisposing natural features from the earliest (probably Gravettian) phases (Fernandes et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the inclusion of natural features has been well documented for some time, with the exception of Ogawa (2005; 2012) and Brot (2010) it has largely been listed simply as a peculiar characteristic of Palaeolithic art to the extent that its potential for understanding the appearance and development of figurative art has not been fully explored. Moreover, despite Hodgson (2003a,b; 2006a,b; 2008; 2013b) and Alpert (2009) having drawn attention to the phenomenon in relation to visual science, it has still not been sufficiently investigated in the present context (see also Dobrez 2010–11; Dobrez & Dobrez 2013; Halverson 1992a,b; Hodgson 2000a,b; 2003a,b; 2006a,b; 2008; 2013a,b; Hodgson & Helvenston 2006a; Hodgson & Watson 2015; Hudson 1998; Kennedy & Silver 1974).…”
Section: Introductionmentioning
confidence: 99%
“…This preference, however, is thought to be far more likely the result of how anatomically modern humans have evolved to visually process animals (e.g. Hodgson 2008Hodgson , 2013Hodgson , 2014Dobrez and Dobrez 2013;Hodgson and Watson 2015). Profiles can more easily show the visually diagnostic characteristics of a particular animal (i.e.…”
Section: Terra Australis 48mentioning
confidence: 99%